SELF-REPORTED SLEEP QUALITY AND ITS ASSOCIATION WITH DEMOGRAPHIC AND HEALTH-RELATED FACTORS AMONG EMERGENCY DEPARTMENT NURSES - Ferdy Lainsamputty; Dwi Debi Tampa'i; Albert Kalengkongan; Moh. Fahrul (Fakultas Ilmu Keperawatan Universitas Klabat, 2020)
Continual sleep loss and disorder among Emergency Department (ED) nurses may negatively impact the quality of care. ED nurses are expected to act with great pace and accuracy in a crowded and high-risk environment. Detail information regarding sleep quality (SQ) and its components among ED nurses is still limited in Indonesia. The study aimed to explore SQ of ED nurses and its relation to demographic and health-related factors. This study utilized a cross-sectional, correlational descriptive design with 65 samples recruited using total sampling technique from 3 EDs in Central Sulawesi. Descriptive statistics and bivariate analysis were performed to examine the association between variables. Global PSQI score was 5.5±2.0 with the prevalence of poor sleepers was 43.1%. Only body mass index (BMI) had correlation with SQ (r=0.26; p<0.05). ED nurses are recommended to reach the ideal body weight to get a bigger chance of having a better sleep. Further studies are required to evaluate interventions that might enhance SQ of ED nurses.